1989
DOI: 10.1016/1010-7940(89)90059-6
|View full text |Cite
|
Sign up to set email alerts
|

Acquired coarctation due to calcified thrombus in atherosclerosis of the descending thoracic aorta Two cases and a review

Abstract: An extremely rare manifestation of atherosclerosis is described. Two women, aged 57 and 55, presented with upper extremity hypertension and diminished femoral pulses. Plain radiography and total angiographic visualization of the aorta demonstrated focal highly obstructing intraluminal masses containing heavy flocculent calcification in the upper descending thoracic (case 1) and the thoracoabdominal aorta (case 2) producing a significant pressure gradient. The acquired coarctation due to calcified thrombus was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Coral reef aorta is essentially treated by conventional surgery comprising thromboendarterectomy, resection of the calcified thrombus and graft replacement of the aorta, or placement of a thoracoabdominal bypass graft [1][2][3][4][5][6]. These direct aortic surgeries are more invasive, and some authors have described an operative mortality rate of 8.7-11.6% and a 13.9-15.9% rate of postoperative complications requiring corrective surgery [2,5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coral reef aorta is essentially treated by conventional surgery comprising thromboendarterectomy, resection of the calcified thrombus and graft replacement of the aorta, or placement of a thoracoabdominal bypass graft [1][2][3][4][5][6]. These direct aortic surgeries are more invasive, and some authors have described an operative mortality rate of 8.7-11.6% and a 13.9-15.9% rate of postoperative complications requiring corrective surgery [2,5].…”
Section: Discussionmentioning
confidence: 99%
“…Axillofemoral extra-anatomical bypass grafting takes less operative time, a shorter period under anesthesia and a smaller skin incision than other direct aortic therapies [1][2][3][4][5][6]8] and it does not require aortic cross clamping that can confer cardiac after loading. Donaldson et al reported an operative mortality rate of 1.1% for axillofemoral bypass grafting [9].…”
Section: Discussionmentioning
confidence: 99%
“…6 In most cases, thrombus formation involves the thoracic segment. 5,7 As with the present case, adults should present to the cardiovascular or hypertension clinic with resistant upper extremity hypertension.…”
Section: Discussionmentioning
confidence: 63%
“…4,5 A literature search of Englishlanguage journals over the last 35 years have turned up cases only in paediatric patients. 6,7 For example, infants with classical features of aortic coarctation were found instead to have aortic thrombus formation in association with umbilical artery catheter placement.…”
Section: Discussionmentioning
confidence: 99%
“…Very few case reports of acquired atheromatous coarctation of aorta has been reported, but the patients were usually treated surgically in these case reports [5][6][7]. In our case, we had performed CT angiography one week prior to the current admission and hence we knew the diagnosis beforehand.…”
Section: Discussionmentioning
confidence: 99%